This Woman Is a Father? The Albricani on a Puzzle about Relations - Hansen, Heine (Vivarium, 2022)
Medieval philosophers had a predilection for using the correlative pair father and son as an illustrative example in their discussions of relations. The use of this example has sometimes led to charges of confusion on the grounds that fatherhood and sonship are not proper converses. The present article shows how a group of twelfth-century philosophers from the milieu around the logician Alberic of Paris handled the problems arising from the use of this illustrative example which they had inherited from their ancient and late-ancient predecessors.